E-Marketplace Usaha Mikro Kecil Dan Menengah (UMKM) Catering Untuk Wilayah Jakarta - Andi Saryoko; Lutfiyah Lutfiyah (Paradigma, 2021)
Many systems and applications are made to help and simplify an activity. Likewise with the ordering system and catering ordering facilities which also take advantage of current technological developments. The process of ordering and conveying information about catering for the Jakarta area is still simple, the promotion is only by word of mouth, from personal acquaintances, or marketing through brochures to prospective customers whose market will be narrower than the internet media. Currently, no e-marketplace site specializes in catering businesses. So that their products have not been known to many people, and their conventional means of product promotion are only through brochures, business cards, or mouths of mouths. That way, the existence of e-marketplace catering can open up opportunities for catering managers in marketing their products to the wider community through the website. The system development model used to design and develop this application is the waterfall model. And this e-marketplace catering system was designed and developed using the programming language PHP, HTML, CSS using the Mysql Database. With the e-marketplace system, it can make it easier for catering businesses to promote their products to the wider community and make it easier for customers to find catering information effectively and efficiently. Using the e-marketplace system makes it easier for catering managers to manage product data collection and manage transaction data in serving customers.